2021
DOI: 10.1038/s41598-021-03159-1
|View full text |Cite
|
Sign up to set email alerts
|

People that score high on psychopathic traits are less likely to yawn contagiously

Abstract: Considerable variation exists in the contagiousness of yawning, and numerous studies have been conducted to investigate the proximate mechanisms involved in this response. Yet, findings within the psychological literature are mixed, with many studies conducted on relatively small and homogeneous samples. Here, we aimed to replicate and extend upon research suggesting a negative relationship between psychopathic traits and yawn contagion in community samples. In the largest study of contagious yawning to date (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 93 publications
2
9
0
Order By: Relevance
“…Instead, the attentional bias hypothesis predicts that YC is merely linked to the higher levels of social attention that observers devote to more relevant subjects (i.e., familiar or dominant) 25 . More recently, Gallup et al 26 found that those people scoring high levels of psychopathic traits, which are associated with reduced affective empathy, also showed low levels of YC, with the yawn response not depending on the attentional level. Although this dualistic conceptual approach is present in literature, the two aspects are difficult to disentangle since probably both attentional and affective processes play a role in the modulation of YC 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the attentional bias hypothesis predicts that YC is merely linked to the higher levels of social attention that observers devote to more relevant subjects (i.e., familiar or dominant) 25 . More recently, Gallup et al 26 found that those people scoring high levels of psychopathic traits, which are associated with reduced affective empathy, also showed low levels of YC, with the yawn response not depending on the attentional level. Although this dualistic conceptual approach is present in literature, the two aspects are difficult to disentangle since probably both attentional and affective processes play a role in the modulation of YC 20 .…”
Section: Introductionmentioning
confidence: 99%
“…While some experimental studies have reported emotional contagion among ravens [ 49 , 50 ], to date, there is no evidence for this capacity among budgerigars. Instead, contagious yawning may be tied to bodily synchrony only [ 75 ], which budgerigars display when interacting with conspecifics [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same was true for overall yawn frequency, except in the case of the amphibian and mammal conditions. The attentional checks to the pairing of yawn and non-yawning stimuli produced a robust response, with a comparably high rate of yawn contagion (69%) to a recent online study on intraspecific yawn contagion using compiled video clips [ 27 ]. Contrary to our predictions, however, neither phylogenetic proximity nor domestication/social closeness of the yawning stimuli enhanced this response.…”
Section: Discussionmentioning
confidence: 99%
“…Psychological experiments on humans have consistently found that people yawn in response to seeing, hearing, and even thinking about other people yawning [ 5 , 24 , 25 ], while individual differences in this response are related to variability in biobehavioral synchrony [ 26 , 27 ]. Yawn contagion is also common among non-human great apes, including chimpanzees [ 28 , 29 ], bonobos [ 30 , 31 ], and orangutans [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation